Comparative Effectiveness of Acupuncture and Antiarrhythmic Drugs for the Prevention of Cardiac Arrhythmias: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Li, Yanda; Barajas-Martinez, Hector; Li, Bo; Gao, Yonghong; Zhang, Zhenpeng; Shang, Hongcai; Xing, Yanwei; Hu, Dan (Frontiers in Physiology, 2017)
Introduction and Objectives: This study was designed to systematically evaluate the effectiveness of acupuncture treatment for arrhythmia compared to existing drug therapy. Methods: Randomized controlled trials（RCTs） were identified through searches of the MEDLINE, CNKI, Embase, and Cochrane databases (1970 through 2016) and hand searches of cross-references from original articles and reviews.Clinical trials that randomized arrhythmia patients to acupuncture therapy versus conventional drugs, sham acupuncture, or bed rest were included for analysis. Results: A total of 13 trials with 797 patients met the criteria for analysis. The results of the meta-analysis showed no statistically significant difference between acupuncture and conventional treatment for paroxysmal supraventricular tachycardia (PSVT) (n=203; RR, 1.18; 95% CI 0.78 to 1.79; I2=80%; P=0.44).. However, in the ventricular premature beat (VPB) group, it showed a significant benefit of acupuncture plus oral administration of anti-arrhythmic drug (AAD) on response rates compared with the oral administration of AAD (n=286; RR, 1.15; 95% CI 1.05 to 1.27; I2=0%; P=0.002). Finally, when compared with the sinus tachycardia (ST) cases without any treatment, acupuncture has benefited these patients (n=120; MD, 18.80, 95% CI 12.68 to 24.92; I2=81%; P<0.00001). Conclusions: In summary, our meta-analysis demonstrates that clinical efficacy of acupuncture is not less than AAD for PSVT. Furthermore, in sub-group analysis, acupuncture with or without AAD, shows a clear benefit in treating VPB and ST. However, more definitive RCTs are warranted to guide clinical practice.